Retrofit design on lighting system - Madihi, A. (University Malaysia Sarawak, UNIMAS., 2006)
This project is on quantity and the better arrangement of bulb according to the suitability of illumination level required. The illumination level should be emphasized since it will affect the workers performance, workers health and may reduce electric usage. Therefore, the retrofitting activities can reduce cost of electric consumption and cost maintenance.